Gene quantitation by a competitive quantitative PCR technique using a homologous standard - Yaacob, Nik Soriani; Nor, Norazmi Mohd (2002)
The project aimed to develop a quantitative PCR technique to accurately quantity gene expression. We tested the accuracy of the method by determining the expression levels of the transcription factor, PPARy. This was done firstly in a mock system (utilizing cloned PPARy in a plasmid with known concentrations) and later on activated monocytes. The method utilized a homologous internal standard in a competitive PCR. This method has the advantage over using housekeeping genes as control since the latter requires different primers and amplification conditions. The current method also has advantage over using PCR MIMIC which may have different amplification efficiency due to the different gene fragment used. The homologous standard was constructed from the same target gene with a slightly shorter length to allow for visualization and analysis following competition with the target gene. The mock experiment showed that the method worked successfully. Using cDNA prepared from activated monocytes we were also able to show that it is useful for determining changes in the levels of PPARy expression in cells expressing the transcription factor.